Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.2146/ajhp170534
|View full text |Cite
|
Sign up to set email alerts
|

Treatment ofAspergillus fumigatusinfection with posaconazole delayed-release tablets

Abstract: A 13-year old patient with CF was successfully treated for an infection with posaconazole delayed-release tablets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
2
0
1
Order By: Relevance
“…A case study of a 13-year-old male patient with CF treated with posaconazole tablets for A. fumigatus infection also demonstrated that plasma trough concentrations of >1 mg/L were attained with a dose of 300 mg, along with improved lung function and eradication of the organism. 24 However, despite these positive experiences thus far, there have been no published pharmacokinetic data to support dosing specific to children with CF, including younger children, and especially in the context of altered pharmacokinetics in this population.…”
Section: Discussionmentioning
confidence: 99%
“…A case study of a 13-year-old male patient with CF treated with posaconazole tablets for A. fumigatus infection also demonstrated that plasma trough concentrations of >1 mg/L were attained with a dose of 300 mg, along with improved lung function and eradication of the organism. 24 However, despite these positive experiences thus far, there have been no published pharmacokinetic data to support dosing specific to children with CF, including younger children, and especially in the context of altered pharmacokinetics in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Higher posaconazole concentrations were found to be correlated with lower Aspergillus Immunoglobulin E levels [150]. Posaconazole oral formulations, especially the delayed-release tablet, exhibited satisfactory exposure in children (median age 13 years, range 3-17 years) with CF and was proven to be generally safe and well tolerated [151]. Overall, the posaconazole delayed-release tablet appears to be a suitable antifungal agent in patients with CF due to the improved absorption and wide intrinsic distribution into the lung tissue.…”
Section: Patients With Cystic Fibrosismentioning
confidence: 95%
“…Описано успешное применение таблетированной формы позаконазола для терапии 13летнего паци ента с муковисцидозом и инфекцией A. fumigatus [104], а также случай эффективной терапии 30летней паци ентки с ОМЛ и необходимостью проведения аллоген ной ТГСК, у которой развился мукормикоз (вызванный Rhizomucor pusillus) с поражением легких и ЦНС. У этой пациентки была проведена хирургическая санация и на значена СПП позаконазола, которая в связи с низкими концентрациями в плазме (0,22 мг/л) была заменена на таблетированную форму позаконазола, которая по зволила достичь достаточных концентраций препарата (> 2 мг/л) при использовании дозы 400 мг/сут, так как стандартная доза 300 мг/сут не обеспечила создание в плазме целевой концентрации (0,45 мг/л) [105].…”
Section: терапия рефрактерных форм игиunclassified